Positive Solutions for Boundary Value Problems of Singular Fractional Differential Equations - Zhanbing Bai; Weichen Sun; Weihai Zhang (Abstract and Applied Analysis)
In this paper, by using a fixed point theorem, we investigate the existence of a positive solution to the singular fractional boundary value problem , , where , , , is Caputo fractional derivative, is singular at the value 0 of its arguments , and satisfies the Lipschitz condition.